Influence of the fractions isolated from Gentiana algida Pall. on the state of cellular and humoral chains of immune response - Y. R. Budaeva; V. B. Khobrakova (Acta Biomedica Scientifica, 2015)
The immune modulatory effect of fractions isolated from the aerial part of Gentiana algida Pall. has been established in experiments on the СВА mice in respect of cellular and humoral immune response at immune suppression caused by azathioprine. The introduction of testfractions (polysaccharide, ethyl acetate, chloroform, butanol) to mice increased the number of the antibody forming cells and index of hypersensitivity reaction of slow type compared with the level of suppression. The most immune modulating effect in respect of cellular and humoral immune response at immune suppression caused by azathioprine has polysaccharide fraction and an ethyl acetate fraction containing phenolic substances. The presence of marked immune modulating properties of the studied remedies in experimental immune suppression allow to recommend them for introduction into the medical practice for the prevention and treatment of immune deficiency conditions, as well as to conduct targeted search of new efficient and low-toxic immune correcting plant preparations.